2016
DOI: 10.5507/bp.2016.014
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of hospital-acquired pneumonia: Results of a Central European multicenter, prospective, observational study compared with data from the European region

Abstract: Background. Hospital-acquired pneumonia (HAP) is associated with high mortality. In Central Europe, there is a dearth of information on the prevalence and treatment of HAP. This project was aimed at collecting multicenter epidemiological data on patients with HAP in the Czech Republic and comparing them with supraregional data. Methods. This prospective, multicenter, ob servational study processed data from a database supported by a Czech Ministry of Health grant project. Included were all consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 30 publications
(33 reference statements)
2
21
0
2
Order By: Relevance
“…Despite progress in modern medical techniques and clinical application of various surgical operations, nosocomial infections (NIs) is considered as a major risk factor for the prognosis of patients [1].It is also notable that, NIs might not only be, directly or indirectly, the critical cause the death of patients, but also directly affect the treatment or operation of the patients and prolong their hospitalization. The primary objective of present study was investigate the rate of nosocomial infections (NIs) in two type of ICU (internal and medical surgery), and analysis the related risk factors NIs we observed that, infection (positive culture) incidence between internal ICU and MS-ICU was 27.2% and 10.2%from 2015 to 2016, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in modern medical techniques and clinical application of various surgical operations, nosocomial infections (NIs) is considered as a major risk factor for the prognosis of patients [1].It is also notable that, NIs might not only be, directly or indirectly, the critical cause the death of patients, but also directly affect the treatment or operation of the patients and prolong their hospitalization. The primary objective of present study was investigate the rate of nosocomial infections (NIs) in two type of ICU (internal and medical surgery), and analysis the related risk factors NIs we observed that, infection (positive culture) incidence between internal ICU and MS-ICU was 27.2% and 10.2%from 2015 to 2016, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that there was a statistically significant difference between the adequacy of the antibiotic treatment and the mortality of patients suffering from ventilator-associated pneumonia. Thus, if the causative bacteria were resistant to the initial antibiotic therapy, the mortality reached 46%, while in case of susceptible bacterial strains it was 27% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 The microbiological epidemiology of HAP/VAP varies widely, but the role of Enterobacteriaceae, mainly represented by Klebsiella pneumoniae isolated in up to one-third of cases, is well established. [5][6][7] In this setting, the emergence of infections caused by carbapenem-resistant Enterobacteriaceae (CRE) represent an alarming problem due to the lack of available therapeutic options, leading to inadequate antibiotic treatment and increased mortality. 8,9 Limited data regarding the optimal antimicrobial regimen for the treatment of HAP/VAP due to CRE are available.…”
mentioning
confidence: 99%